Influence of Technology on Public Administration: Opportunities and Challenges - Nor, Abdirizak Husein; Malenge, Ezekiel Ingudia (UIN Sunan Gunung Djati Bandung, 2025)
This study examines the impact of technology on public administration, emphasising both its transformative opportunities and the challenges it presents. In the context of increasing digitisation, the research explores how innovations such as e-governance, automation, and data-driven decision-making influence efficiency, transparency, and service delivery within government institutions. The purpose of the study is to assess how technological tools contribute to administrative effectiveness and citizen engagement while identifying barriers that hinder their full implementation. A quantitative research design was employed, using an online questionnaire completed by 70 government employees from different departments, supplemented by secondary data from local and international reports, scholarly articles, and official websites on technology and governance. The findings reveal that technology significantly improves service delivery, operational efficiency, and public participation in governance. However, issues such as inadequate digital infrastructure, limited digital literacy among public officials, and cybersecurity risks constrain the effective use of these innovations. The study concludes that to fully harness the benefits of technology in public administration, governments must invest in robust digital infrastructure, provide continuous training for public servants, and implement policies promoting digital literacy and data protection. Addressing these challenges will strengthen institutional performance, enhance citizen trust, and ensure that public administration adapts effectively to the evolving demands of modern governance.